EL CONTRATO ESPECIAL EMERGENTE Y SU INCIDENCIA EN LA VULNERACION DEL PRINCIPIO DE ESTABILIDAD LABORAL EN LA LEGISLACION ECUATORIANA. - SANCHEZ JARAMILLO, THALIA MICHELLE (2021)
The present degree thesis is entitled "The emergent special contract and its incidence in the violation of the principle of labor stability of the worker in Ecuadorian legislation", the same that arises from the need due to the analysis carried out on Article 19 of the Contract Emerging special, in force in the Organic Law of Humanitarian Support, a law that was promulgated from the serious economic crisis caused by the pandemic called COVID -19. This new contract retakes in Ecuador the fixed-term contract that was repealed in 2015. This new contract was established in order to maintain sources of employment, however, the conditions under which this emerging special contract is celebrated allow it to be Give abuse by the employer in the employment relationship, as there is a wide margin for violations of workers' rights. Job stability is one of the most important social achievements that workers have, since it brings economic stability to workers, because by having a stable job, they have permanent income that can cover their basic needs and those of their family , with the incorporation of the emergent special Contract in the Ecuadorian legal system seriously violates the principle of Labor Stability of the worker, guaranteed in the Constitution of the Republic of Ecuador. 4 In the development of the thesis, materials and methods were applied to develop this research and interviews and surveys were also carried out with prominent professionals of the Law, results that served to propose a project of legal reform to the Organic Law of Humanitarian Support, incorporating norms that guarantee that in emergent situations the rights of workers are not violated, nor principles of Labor Law.